Effects of Weight Loss on Foot Structure and Function in Obese Adults: A Pilot Randomized Controlled Trial - Song, Jinsup (Gait Posture, 2014)
OBJECTIVE: To investigate the effects of weight reduction on foot structure, gait, and dynamic plantar loading in obese adults. DESIGN: In a 3-month randomized-controlled trial, participants were randomized to receive either a weight loss intervention based on portion-controlled meals or a delayed-treatment control. PARTICIPANTS: 41 adults (32 F, 9 M) with a mean + SD age of 56.2 + 4.7 years and a BMI of 35.9 + 4.2 kg/m2. MEASUREMENTS: Arch Height Index (AHI), Malleolar Valgus Index (MVI), spatial and temporal gait parameters, plantar peak pressure (PP) and weight were measured at baseline, 3, and 6 months. RESULTS: The intervention group experienced significantly greater weight loss than did the control group (5.9 ± 4.0 kg versus 1.9 ± 3.2 kg, p = 0.001) after 3 months. There were no differences between the groups in anatomical foot structure or gait. However, the treatment group showed a significantly reduced PP than the control group beneath the lateral arch and the metatarsals 4 (all P values < .05) at 3 months. The change in PP correlated significantly with the change in weight at the metatarsal 2 (r=0.57, p=0.0219), metatarsal 3 (r=0.56, p=0.0064) and the medial arch (r=0.26, p<0.0001) at 6 months. CONCLUSION: This was the first RCT designed to assess the effects of weight loss on foot structure, gait, and plantar loading in obese adults. Even a modest weight loss significantly reduced the dynamic plantar loading in obese adults. However, weight loss appeared to have no effects on foot structure and gait.